Nanogravimetric and Optical Characterizations of Thrombin Interaction with a Self-Assembled Thiolated Aptamer. (9th May 2016) - Politi, Jane; Rea, Ilaria; Nici, Fabrizia; Dardano, Principia; Terracciano, Monica; Oliviero, Giorgia; Borbone, Nicola; Piccialli, Gennaro; De Stefano, Luca
Abstract : Efficient biorecognition of thrombin (TB), a serine protease with crucial role in physiological and pathological blood coagulation, is a hot topic in medical diagnostics. In this work, we investigate the ability of synthetic thrombin aptamer (TBA), immobilized on a gold substrate, to bind thrombin by two different label-free techniques: the quartz crystal microbalance (QCM) and the spectroscopic ellipsometry (SE). By QCM characterization in the range from 20 to 110 nM, we demonstrate high specificity of TBA-TB interaction and determine affinity constant (K d ) of17.7 ± 0.3  nM, system sensitivity of0.42 ± 0.03  Hz nM −1, and limit of detection (LOD) of240 ± 20  pM. The interaction between TBA and TB is also investigated by SE, an all-optical method, by quantifying the thickness increase of the TBA film assembled on gold substrate. AFM characterization of TBA and TB molecules deposited on flat silicon surface is also supplied.